2018
DOI: 10.1039/c8dt01946k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, cytotoxic activity and DNA interaction studies of new dinuclear platinum(ii) complexes with an aromatic 1,5-naphthyridine bridging ligand: DNA binding mode of polynuclear platinum(ii) complexes in relation to the complex structure

Abstract: [{Pt(L)Cl}2(μ-1,5-nphe)]2+ complexes have been reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…In the aromatic region, the 1 H NMR spectra of C1 complex consists of four characteristic group of signals corresponding to eight protons of the three condensed aromatic rings in N‐ heterocycle, with resonances shifted downfield in respect to those for the protons of the uncoordinated 1,7‐phen ligand. The observed downfield shifting for the aromatic protons in the N ‐heterocyclic ligand after their platination can be ascribed to a delocalization of the charge deficiency (cation formation by Pt(II) coordination) throughout all the rings in the molecule as anticipated . Considering all aromatic protons, the significant values of Δ( 1 H) coord coordination shifts are +0.18 and +0.72 ppm for C1 complex.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…In the aromatic region, the 1 H NMR spectra of C1 complex consists of four characteristic group of signals corresponding to eight protons of the three condensed aromatic rings in N‐ heterocycle, with resonances shifted downfield in respect to those for the protons of the uncoordinated 1,7‐phen ligand. The observed downfield shifting for the aromatic protons in the N ‐heterocyclic ligand after their platination can be ascribed to a delocalization of the charge deficiency (cation formation by Pt(II) coordination) throughout all the rings in the molecule as anticipated . Considering all aromatic protons, the significant values of Δ( 1 H) coord coordination shifts are +0.18 and +0.72 ppm for C1 complex.…”
Section: Resultsmentioning
confidence: 57%
“…Polynuclear platinum(II) complexes, in which two or three platinum centers are bridged by polyamines or diferent N ‐heterocycles, represent a novel class of antitumor agents . Earlier results of investigation showed that some of the dinuclear platinum(II) complexes with N ‐heterocycles bridging ligands are more effective in vitro than cisplatin in several tumor cell lines …”
Section: Introductionmentioning
confidence: 99%
“…Rajković et al in 2018 synthesized new 1,5-naphthyridine-bridged (1,5-nphe) dinuclear platinum(II) complexes, with the general formula [{Pt(L)Cl}2(μ-1,5-nphe)](ClO 4 ) 2 , and evaluated the in vitro cytotoxic activity of these complexes against three tumor cell lines, murine colon carcinoma (CT26), murine mammary carcinoma (4T1) and murine lung cancer (LLC1) and two normal cell lines, murine mesenchymal stem cells (MSC) and human fibroblast (MRC-5) cells [ 135 ].…”
Section: Applications Of 15-naphthyridinesmentioning
confidence: 99%
“…The cis ‐[PtCl(NH 3 ) 2 (naph)]NO 3 complex has shown enhanced cytotoxic effects on human tumor cells that are resistant to oxaliplatin (LoVo‐OXP) . Analyzing the biological activity of the synthesized dinuclear platinum(II) complexes [{Pt(L)Cl} 2 ( μ ‐1,5‐nphe)] 2+ (L=2NH 3 ; ethylenediamine; 1,2‐propylenediamine; trans ‐1,2‐diaminocyclohexane; 1,3‐propylenediamine; 2,2‐dimethyl‐1,3‐propylenediamine; 1,3‐pentanediamine and 1,5‐nphe=1,5‐naphthyridine) it was found that murine colon, breast and lungs cancer cell lines are most sensitive to the effect of [{PtCl(NH 3 ) 2 } 2 ( μ ‐1,5‐nphe)] 2+ and [{Pt(en)Cl} 2 ( μ ‐1,5‐nphe)] 2+ . However, the antitumor effects of these complexes are minor compared to the effects of cisplatin.…”
Section: Introductionmentioning
confidence: 99%
“…All investigated complexes, unlike cisplatin, weakly reduce the viability of mesenchymal stem cells and human fibroblasts, which may indicate their potentially lower toxicity. By examining the possible mechanism of cell death, it was found that the corresponding platinum(II) complexes induce apoptosis of mouse colon cancer tumor cells …”
Section: Introductionmentioning
confidence: 99%